The needs of patients with diabetes for the prevention and treatment of foot complications in Thailand: A qualitative descriptive study - Piyawan Kanan; Boonying Siribamrungwong; Thipapron Tarawanich; Saritpat Arapinth; Phunyada Napunnaphat (Belitung Nursing Journal, 2023)
Background: Inadequate diabetes self-management leads to foot infections and lower extremity amputations. Effective self-care, supported by nurse-provided information, is crucial, particularly in foot care. However, the current approach in Thailand focuses more on what nurses want patients to know rather than addressing patients’ actual needs. Consequently, nurses might misunderstand their patients' perspectives. Hence, nurses need to grasp patients’ needs for successful foot care behavior. Objective: This study aimed to explore the needs of patients with diabetes regarding the prevention and treatment of foot complications. Methods: The study employed a qualitative descriptive design. Thirty participants classified as high risk for foot ulcers were purposively selected from Thailand's university hospitals. Focus group discussions were used for data collection between June and July 2021. Verbatim transcription and content analysis were carried out for data analysis. Results: Four emergent themes highlighted patients’ needs: 1) information-giving, 2) proactive foot screening with foot-care affirmation, 3) foot care services, and 4) relieving foot burdens and limb loss. Conclusion: Nurses should change their mindset to care for and continually understand patients' needs. This involves adapting educational strategies like the teach-back method and coaching while providing skill training. Offering diverse service platforms, both online and onsite education programs and counseling, is essential. Additionally, ensuring accessibility and affordability, such as establishing after-hours clinics and supplying foot care toolkits, remains crucial.